2015
DOI: 10.1149/2.f06154if
|View full text |Cite
|
Sign up to set email alerts
|

Phosphors by Design: Approaches Toward the Development of Advanced Luminescent Materials

Abstract: The rapid discovery of new phosphors is necessary to enhance the next generation of solid-state lighting by improving device color quality and decreasing cost. This article reviews key non-conventional methods used to expedite novel phosphor discovery. The methods reviewed (with selected examples) include experimental methods such as combinatorial screening, and combined experimental and computation-based methods such as genetic-algorithm-assisted combinatorial chemistry and certain multi-objective optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In the search for new phosphors, research has shown one viable method for identifying materials with a high Φ is to find structurally rigid host compounds with high atomic connectivity 16 . These characteristics enhance Φ by inhibiting soft phonon modes that lead to non-radiative relaxation, thereby increasing the propensity for photon emission.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for new phosphors, research has shown one viable method for identifying materials with a high Φ is to find structurally rigid host compounds with high atomic connectivity 16 . These characteristics enhance Φ by inhibiting soft phonon modes that lead to non-radiative relaxation, thereby increasing the propensity for photon emission.…”
Section: Introductionmentioning
confidence: 99%
“…Designing an effective phosphor exhibiting bright luminescence requires careful consideration of the crystal structure to tune interactions between luminescent centers and the host lattice as well as to suppress nonradiative recombination pathways. , A particularly useful host crystal structure that exhibits a low-phonon cutoff energy and limits cross-relaxation mechanisms is the tetragonal matlockite PbFCl structure (space group P 4/ nmm) . In this article, we examine LaOCl, which adopts the PbFCl structure (as depicted in the inset of Figure S1), as a host lattice for multiple luminescent centers. In this structure, infinite sheets of (LaO) n n + and Cl – ions are alternated along the crystallographic c direction. The trivalent lanthanum cations have a local coordination environment described by C 4 v symmetry wherein each La-ion resides in a monocapped square antiprism defined by four oxygen atoms in an underlying plane (with a La–O bond distance of 2.39 Å) and five chloride ions in the layers above.…”
Section: Resultsmentioning
confidence: 99%
“…Designing an effective phosphor exhibiting bright luminescence requires careful consideration of the crystal structure to tune interactions between luminescent centers and the host lattice as well as to suppress nonradiative recombination pathways. 20,21 A particularly useful host crystal structure that exhibits a low-phonon cutoff energy and limits cross-relaxation mechanisms is the tetragonal matlockite PbFCl structure (space group P4/nmm). 22−24 In this article, we examine LaOCl, which adopts the PbFCl structure (as depicted in the inset of Figure S1), as a host lattice for multiple luminescent centers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In contrast, the structural rigidity of a phosphor is closely related to its thermal stability and a higher structural rigidity can effectively suppress the nonradiative transitions, which in turn gives rise to a phosphor with high efficiency. However, it is often difficult to identify compounds that are more structurally rigid than others [40] . A more tractable method for determining structural rigidity is to evaluate the Debye temperature of the material [41] .…”
Section: Materials Properties Predictionmentioning
confidence: 99%